Ethnomathematics Form A Wide Range Of Perspective - Wahyuni Wahyuni; Frida Marta Argareta Simorangkir; Izwita Dewi (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2023)
Mathematics belongs to its own thinkers, and every thinker has their own culture. So mathematics has an attachment to culture. Ethnomathematics emerged as a link between mathematics and culture. Ethnomathematics continues to evolve and embrace a wider range of studies with a cultural and social center. So the shift in focus towards the ethnomathematical paradigm is inevitable. This study identifies several philosophers' thoughts about the perspective of research results in the field of ethnomathematics. The debating paradigm in culturally based mathematical research. This study aims to describe ethnomathematics from various perspectives; the research method used is literature study. The results of this study can be summarized as follows: There are two paradigms related to the study of ethnomathematics, namely ethnomathematics as a cultural practice and ethnomathematics as a theory to analyze something different. There are various perspectives in ethnomathematical research, (1) there are several perspectives on ethnomathematics as a cultural practice, including ethnomathematics as a mathematicizing activity, the NUC system, mathematical analysis activities, mathematics projects, ethics, and ethnomathematics or mathematics. (2) as a theory, ethnomathematics can be looked at from different points of view, such as the QRS system, analogy mathematical activity, location interpretation, emic, and ethnomathematics and mathematics